The Analysis of the Usage of Emojis on Instagram Account @Englishwithlucy - Ni Putu Sri Galuh Lestari; Pande Agus Adiwijaya; Luh Made Dwi Wedayanthi (CV. Tirta Pustaka Press, 2024)
This study investigates the role of emojis in language learning on social media, with a particular focus on the Instagram account @englishwithlucy. The research aims to provide insights for educators and learners by analyzing the description, interpretation, and explanation of emoji usage. Employing a qualitative approach, the study uses Norman Fairclough's Critical Discourse Analysis (CDA) model and collects data through documentation and netnography methods. The analysis reveals significant findings regarding the communication strategies employed by @englishwithlucy and their impact on language learners. The primary objectives were to examine the types, frequency, and integration of emojis in the account's discourse. Key findings include: 1) Emojis serve as crucial communication tools that enhance engagement and facilitate effective communication by conveying emotions and creating relatability, consistent with previous research. 2) Emojis reinforce messages and contextualize vocabulary, aiding in comprehension and retention, which aligns with existing studies. 3) The account deliberately avoids negative emojis to maintain a positive and encouraging tone, fostering a supportive learning environment, as supported by current literature. 4) Social and cultural contexts significantly influence emoji usage, with the account selecting emojis that have common interpretations across cultures to ensure clarity and inclusivity. Overall, the strategic use of emojis on @englishwithlucy not only enhances engagement and communication but also contributes to a vibrant and interactive learning environment. These findings contribute to the growing body of knowledge on the educational significance of emojis and underscore their importance as integral components of language and communication on social media platforms.